Nilai-Nilai Moral Tokoh Bodour pada Novel Zeina Karya Nawal El. Saadawi (Kajian Strukturalisme Genetik) - Febrianisa, Sindy (Universitas Muhammadiyah Gorontalo, 2023)
Moral values in life become one of the important aspects in supporting life, especially social and community life. So that this becomes the main focus point, because there are many deviations in moral values in the Bodour character. So this research has the aim to describe how the form of moral values in the character Bodour in the novel Zeina by Nawal El. Saadawi. The method in this research is descriptive-qualitative method of content analysis with the perspective of Lucien Goldmann's genetic structuralism. The object of this study is the novel Zeina by Nawal El. Saadawi. The focus of this research is in the form of human facts, collective subjects, worldviews, structuring of literary works and dialectical methods which are explanations as analytical tools, which are associated with moral values in the novel. The instrument of this research is the researcher himself. the data analysis technique used by the researcher was reading Zeina's novel by Nawal El. Saadawi. Analyze moral values, enter the results of the analysis, and conclude the results of the analysis. The moral values of the mother figures analyzed in this study are: (1) Honesty, (2) willingness to take responsibility, (3) courage, (4) humility. The research results obtained from data analysis on Zeina's novel by Nawal El. Saadawi, stated that the moral value that stands out is a warning for women to always be able to choose the best environment, choose the right partner. Because it is an important aspect of life. The figure of Bodour herself has given a very significant picture of the role of women in the family, society and state.